2011
DOI: 10.1007/s10735-011-9329-3
|View full text |Cite
|
Sign up to set email alerts
|

Localization and subcellular distribution of prolyl oligopeptidase in the mouse placenta

Abstract: Prolyl oligopeptidase (POP) is a serine endopeptidase which selectively digests a -Pro-X-peptide bond.Our previous study showed that POP mRNA was strongly expressed in the spongiotrophoblast of the mouse placenta at E17.5, suggesting its importance in development. To gain more insight into POP's role during gestation, we investigated its expression using different developmental stages of placenta. As a result of in situ hybridization, we found that localization of POP mRNA changed at E12.5. POP mRNA was strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 61 publications
4
22
1
Order By: Relevance
“…These expression patterns of EGFP mRNA were different from that of the endogenous POP mRNA which was expressed at higher levels in the ovary and placenta (Fig. 1, Matsubara et al, 2010Matsubara et al, , 2011. This indicated that the 914-bp promoter was insufficient to recapitulate the tissue distribution of POP mRNA.…”
Section: Tissue Distribution Of the Egfp Gene In The Transgenic Linesmentioning
confidence: 88%
See 3 more Smart Citations
“…These expression patterns of EGFP mRNA were different from that of the endogenous POP mRNA which was expressed at higher levels in the ovary and placenta (Fig. 1, Matsubara et al, 2010Matsubara et al, , 2011. This indicated that the 914-bp promoter was insufficient to recapitulate the tissue distribution of POP mRNA.…”
Section: Tissue Distribution Of the Egfp Gene In The Transgenic Linesmentioning
confidence: 88%
“…Moreover, we have shown that the mouse POP mRNA was localized to granulosa cells in the ovary (Matsubara et al, 2010) and to spermatids in the testis (Kimura et al, 2002). In the placenta, POP mRNA changed its localization at embryonic day 12.5 (E12.5) from the junctional and labyrinthine zones to the junctional zone alone (Matsubara et al, 2011). These indicate that the POP gene transcription is highly regulated in a tissue-specific manner.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The germ cells were further fractionated into nuclear, membrane, and cytoplasmic subfractions as previously described [8].…”
Section: Isolation Of Germ Cells and Their Fractionation Into Nuclearmentioning
confidence: 99%